1990
DOI: 10.1177/004051759006000101
|View full text |Cite
|
Sign up to set email alerts
|

A New Perspective on Yarn Unevenness: Components and Determinants of General Unevenness

Abstract: A simple analysis of the local linear density of a yarn yields an equation of its overall variance, which has three components: variance of the number of fibers per cross section, variance of the mean local fiber fineness, and that of the mean parameter of fiber inclination relative to yam axis. Further mathematical analysis of the component variances reveals a set of determining factors: the sequence of the fiber ends along the yam, the distribution of the fiber length, fiber fineness and its irregularity, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Therefore, the accelerated points of floating fibers are most likely to move close to the front nip line, which can reduce the yarn unevenness. 24…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…Therefore, the accelerated points of floating fibers are most likely to move close to the front nip line, which can reduce the yarn unevenness. 24…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…All fibers in the yarn are fully extended in parallel along the yarn's length axis. [2][3][4][5][8][9][10] 2. Fiber fineness among different fibers can vary but be independent of fiber length.…”
Section: Assumptionsmentioning
confidence: 99%
“…(8) where w i is the normalised firing strength from layer 3 and {p i , q i , r i } is the parameter set of this node. Parameters in this layer are referred to as consequent parameters.…”
Section: (7)mentioning
confidence: 99%
“…Garde [7] found that the yarn unevenness is more intimately related with the number of thick and thin places than the number of neps. Zeidman et al [8] categorised the factors influencing yarn unevenness in three groups: determinants of the number of fibers per cross-section, determinants of the local mean fiber fineness and determinants of the local mean orientation of fibers. Hunter [9] and Chasmawala et al [10] developed statistical regression equations to predict the unevenness of spun yarns.…”
Section: Introductionmentioning
confidence: 99%